Treatment Priorities of Parents of Children With Cerebral Palsy: A Scoping Review - Zahra Morovati; Saeid Fatorehchy; Seyed Ali Hosseini (Journal of Rehabilitation, 2024)
Objective Cerebral palsy is a group of movement disorders caused by damage to one or more regions of the developing brain. Therapists use different treatment approaches for children with cerebral palsy. It is important to pay attention to the priorities of the parents of these children because they spend most of the time with their children and are fully aware of their needs. The present study aims to investigate the treatment priorities of parents of children with cerebral palsy. Materials & Methods In this scoping review study, a search was first conducted in national and international databases, including SID, PubMed, Scopus, Google Scholar, OT Seeker, and the Bank of Medical Theses of the country. The articles focused on the treatment priorities of parents of children with cerebral palsy and published in English or Persian from 2000 to 2022 were included. The review studies published in other languages were excluded. After assessing the found articles based on the inclusion and exclusion criteria, 12 articles were finally selected for the review. Results The parents of children with cerebral palsy have different priorities. Teaching elf-care skills to the child was one of their most important priorities, which is not dependent on the age and level of gross motor function in children. Other important priorities were mobility and having complete information about treatment services. It seems that all the mentioned priorities are related to each other and paying attention to each one requires checking other priorities. Conclusion The priorities of the parents of children with cerebral palsy are broad and unique. Not all of these priorities are dependent on the age and severity of disability in the children, and can be different per child. It seems necessary to pay attention to the treatment priorities of the parents of these children in the rehabilitation process.